Optimalisasi Strategi Omnichannel: Membangun Keterampilan Pemasaran Digital Siswa SMK Negeri 1 Purwojati - Putri, Puspita Lianti; Riska Nadiya Salsabela (PT. Karya Inovatif Nusantara, 2025)
Omnichannel digital marketing has become an increasingly popular strategy in modern business. This strategy integrates various marketing channels to provide a consistent and seamless experience for customers, both online and offline. The aim of this community service program is to optimize the digital marketing skills of students at SMK Negeri 1 Purwojati through the application of omnichannel strategies. This training program provides insights and practical skills in managing integrated marketing campaigns across various digital platforms. By combining theoretical and practical approaches, students are expected to understand the concept of omnichannel and implement it in real-world scenarios. Evaluations show that most students successfully understood and applied omnichannel marketing strategies in their projects. However, challenges include limited infrastructure and the lack of teacher expertise in this field. This program is expected to contribute to enhancing the preparedness of SMK Negeri 1 Purwojati students to face the workforce, which increasingly relies on omnichannel digital marketing.